Analogy and dialectics: a genealogical comparison of Hegel and Przywara - Haecker, Ryan (2017)
Analogy and dialectics are principles of logic, grammar, and metaphysics for intermediating the elements of theology. Analogy is a grammatical relation that differentiates many distinct terms that remain related by a proportionate similitude, while dialectics is a logical relation that opposes many contradictory theses for the purpose of resolving these contradictions into a synthetic unity of opposites. Each may be abstractly divided by definition but both must be concretely united, through the shared semiotic medium of signs, in the essential relations of the Trinity. The Trinity is the consummate centre in which analogy and dialectics completely coincide. Both principles have been alternatively championed for the purpose of constructing the metaphysical infrastructure of theology: analogy has been presented as a metaphysical-causal principle of the proportionate participation of imperfect analogate in perfect analogon terms; while dialectics has alternatively been presented as an onto-noetic principle that annuls so as to preserve contradictory theses. The champions of analogy and dialectics typically subordinate one to the other: analogy is subordinated to dialectics as an equivocal opposition of theses, while dialectics is subordinated to analogy as a more restricted dialectics between terms. This mutual subordination has been deployed to preserve the purity of analogy and dialectics, but proves to subvert both principles: for when dialectics is subordinated to analogy the force of its contradictory theses can be fossilized in analogy; and when analogy is subordinated to dialectics the bonds of participation between its analogate terms can be broken in dialectics. The broken analogy and the fossilized dialectics that result from such a subordination must inevitably fail because the broken analogy can no more grammatically conjoin its opposed terms than the fossilized dialectics can argumentatively unite its opposites. Since, however, analogy possesses the power to suspend any distinction between terms, and dialectics possesses the power to sublate any opposition between theses, dialectics can erupt from its fossilized form and analogy can only restore its broken bonds in and through the essential relations of the Trinity.